2018
DOI: 10.2147/ijwh.s172669
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled pilot trial of a smoking cessation intervention for US women living with HIV: telephone-based video call vs voice call

Abstract: BackgroundPeople living with HIV smoke at a rate three times that of the general population. This randomized controlled pilot trial tested the feasibility and acceptability of a video-call smoking cessation intervention in women living with HIV and its preliminary efficacy compared with a voice-call smoking cessation intervention. The study focused on women due to a paucity of studies among this population, and women are less likely than men to quit smoking when provided with conventional treatment.MethodsPart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 69 publications
1
68
0
Order By: Relevance
“…These findings suggest that video counselling is an acceptable mode for providing smoking cessation support to rural and remote residents. Similarly, studies among women living with HIV ( Kim et al, 2018 ), Korean American women ( Kim et al, 2016 ), and rural residents that travelled to a clinic to use the video equipment ( Richter et al, 2015 ) have reported that video counselling for smoking cessation is acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that video counselling is an acceptable mode for providing smoking cessation support to rural and remote residents. Similarly, studies among women living with HIV ( Kim et al, 2018 ), Korean American women ( Kim et al, 2016 ), and rural residents that travelled to a clinic to use the video equipment ( Richter et al, 2015 ) have reported that video counselling for smoking cessation is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Three US studies have compared the acceptability of real-time video counselling to telephone counselling ( Kim et al, 2018 , 2016 ; Richter et al, 2015 ) and no studies have compared the acceptability of real-time video counselling to written materials. Two studies measured acceptability using the Client Satisfaction Questionnaire and found no significant differences between the video counselling and telephone counselling groups on acceptability scores ( Kim et al, 2018 , 2016 ). These studies targeted particular groups of smokers, specifically women living with HIV ( Kim et al, 2018 ) and Korean American women ( Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunity to both see and hear the client during video-communication can result in a high level of engagement with the counsellor [17]. Three randomised trials conducted in the USA have compared video counselling to telephone counselling for smoking cessation [18][19][20]. In these studies, video counselling was offered to women living with HIV [18], Korean American women [19] and people living in rural areas [20].…”
Section: Introductionmentioning
confidence: 99%
“…Three randomised trials conducted in the USA have compared video counselling to telephone counselling for smoking cessation [18][19][20]. In these studies, video counselling was offered to women living with HIV [18], Korean American women [19] and people living in rural areas [20]. However, none of these trials examined the connectivity of the video counselling sessions compared to telephone counselling sessions.…”
Section: Introductionmentioning
confidence: 99%